(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this research were 1) to study the concepts and principles of social work in Thai society today, 2) to study the work of social work of ASEAN women association in Kalasin province, 3) to study social work of ASEAN women association in Kalasin province to Buddhist integration. This research was qualitative research. The data were collected from documents, field work, in-depth interview, key informants. Its aim was the concepts and principles of social work. Analysis model of work of ASEAN women association in Kalasin province were found that the concepts and principles of social work in Thai society today was a social work that took place as a form of practice in Thai society of being concrete. This social work was established on the principle of the four bases of sympathy (Sangahavatthu) consisting of 1) charity, generousness, sacrifice, 2) kindly speech, a speech was connected to society, 3) useful conduct to society, creating happiness, the relief of suffering, and 4) participation and behaving oneself properly in all circumstances, acting as a role model for society. The work of social work of ASEAN women association in Kalasin province was social work in the sense of giving benefits to society, exchanged knowledge and experience between groups of successful business people, collaboration for development to expand various project as well as promoting cooperation and working as a network, cultural exchange and tradition between community to community and country to country including organizing joint activity and exchanged for both public and private sectors. Social work of ASEAN women association in Kalasin province to Buddhist integration was consistent with research of donation to support community activity, which was to share happiness with the community, to create benefits for the public consistently, gave equality for everyone, treated everyone as a relative